Protocolo de desenvolvimento de oficinas pedagógicas para o ensino de biologia - Simão, Joaquim Jackson Lisboa (2019)
The creation of a protocol that envisages the operationalization of this tool is a necessary initiative in the field of biological sciences, as well as education. For that, the aim was to develop a methodological protocol related to the implementation of pedagogical workshops in teaching and learning in biology with scientific research. It is a methodological study of protocol development structured in three stages, which are: a) First stage: construction of the preliminary script of the protocol; b) Second stage: adjustments of the script through the integrative review of the literature and determination of the essential and advisable stages; c) Third stage: validation of the content of the protocol through the evaluation of experienced judges in teaching in Biology. The data of the integrative review and the validation of the judges were tabulated using Microsoft Office Excel® for Windows 8 and the statistical program used was the Statistical Package for the Social Sciences (IBM SPSS) version 21, using descriptive and inferential statistics, through absolute and relative frequency, Content Validity Index (CVI≥0.80), Qui-square test and Fisher's exact, with significance considered for values ≤0.05, measure of reliability through Cronbach's alpha (α). The research was approved by the Research Ethics Committee with n. 3.290.764 and CAAE n. 10604219.4.0000.5188. The protocol has three phases and 20 stages, which are: a) Phase I: Characterization and diagnosis (choice of theme, choice of site, preliminary visit, characterization of the target audience, direction of evaluation, diagnostic evaluation, sought strategy with indication of the student, relevance of the subject in the curricular structure, interdisciplinarity and search of subsumption); b) Preparation and implementation of the workshop (collective construction of the workshop, problematization, availability of resources, forecast of the need to make materials, locomotion, staff sizing, workshop application, evaluation of the intended objective and the workshop by the participants); and c) Analysis of the data (characteristics of the data collected and technique of analysis). The integrative review occurred with 25 eligible studies, with seven publications in 2017 and thirteen in the South. The adjustments of the protocol allowed to glimpse nine essential steps and eleven advisable steps. There was a statistical association between preliminary visit with problematization (p=0.031) and workshop evaluation (p=0.009), as well as strategy search with student indication with collective workshop construction (p<0.0001) and problematization (p=0.040), evaluation with data characteristics (p <0.0001) and analysis technique (p <0.0001). In the Delphi I round, the reliability analysis generated α = 0.96 for clarity, α = 0.95 for relevance and α = 0.95 for precision. The reliability test for the general protocol indicated α = 0.98. In the Delphi II stage, α = 0.94 was generated for clarity and α = 0.93 for precision. The overall assessment remained with α = 0.98. All the steps had concordance in the relevance criterion ≥0.80. The qualitative reformulations of the protocol according to the judges' suggestions for IVC ≤0.80 in all the analyzed criteria were related to the modification of disused terms. It was concluded that there was a satisfactory development of the protocol based on professional experience, with its refinements and content validation, indicating a reliable, clear, relevant and accurate product.